1987
DOI: 10.1073/pnas.84.13.4524
|View full text |Cite
|
Sign up to set email alerts
|

The gluconate operon gnt of Bacillus subtilis encodes its own transcriptional negative regulator.

Abstract: The gluconate (gnt) operon ofBacillus subtilis consists of four gnt genes; the second and third genes code for gluconate kinase (gluconokinase, EC 2.7.1.12) and gluconate permease, respectively. A fragment carrying the promoter of this operon (gnt promoter) and the first gene (gntR) was subcloned into a promoter probe vector (pPL603B). Repression of the expression of cat-86 gene, encoded in the vector portion of a constructed plasmid (pgnt2l), that is under the control of the gnt promoter was removed by glucon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
64
0

Year Published

1989
1989
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(65 citation statements)
references
References 17 publications
1
64
0
Order By: Relevance
“…When CT-43 cells were grown in GYS medium containing yeast extract, they selected a third route that relies on the gnt operon that participates in gluconate metabolism. In CT-43, the gnt operon (CH2189 -2191) is composed of gntP (gluconate permease), gntK, and gntZ/gndA (6-phosphogluconate dehydrogenase), and lacks its own transcriptional regulator, which is comparable to the negative regulator gntR in B. subtilis (53). Our RNA-seq results showed that the gnt operon expression level reached a maximum at 7 h, and then gradually decreased.…”
Section: Fig 2 Cog Analysismentioning
confidence: 72%
“…When CT-43 cells were grown in GYS medium containing yeast extract, they selected a third route that relies on the gnt operon that participates in gluconate metabolism. In CT-43, the gnt operon (CH2189 -2191) is composed of gntP (gluconate permease), gntK, and gntZ/gndA (6-phosphogluconate dehydrogenase), and lacks its own transcriptional regulator, which is comparable to the negative regulator gntR in B. subtilis (53). Our RNA-seq results showed that the gnt operon expression level reached a maximum at 7 h, and then gradually decreased.…”
Section: Fig 2 Cog Analysismentioning
confidence: 72%
“…The orf0 encoded a putative protein of 245 amino acids, and the data base search revealed that the ORF0 protein shares 28% identity to GntR, a regulatory protein known as the transcriptional repressor of the gluconate operon in Bacillus subtilis (29). These two proteins exhibited a high similarity of amino acid sequence in the N-terminal region ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…It was first reported that the GntR protein negatively regulates the gnt operon in B. subtilis (29). The GntR-type regulatory proteins involved in the degradation of aromatic compounds are also reported to be repressors (18,31).…”
Section: Discussionmentioning
confidence: 99%
“…GntR and some of its relatives, including PdhR and LctR, are autoregulatory, binding to operator sequences comprising inverted repeats in their own promoters (Fujita and Fujita, 1987;Fujita and Miwa, 1989;Quail et al, 1994). The greatly increased whiH transcription detected in a whiH mutant indicates a negative autoregulatory circuit, with the simplest hypothesis being direct autoregulation.…”
Section: Evidence Of Autoregulation Of Whih Expressionmentioning
confidence: 99%